Peran Serta Masyarakat, Dunia Usaha dan Pemerintah Daerah Dalam Perluasan Kesempatan Kerja Berdasarkan Slogan CIANJUR JAGO dan Visi, Misi Kabupaten Cianjur (Dikaji Menurut Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan) - Ahmad Hunaeni Zulkarnaen (Jurnal Hukum Mimbar Justitia, 2017)
ABSTRACTThe participation of the society, business community and the Government of Cianjurregency in creating the expansion of employment by the slogan "Cianjur Jago" in linewith the Vision of Cianjur Regency 2016-2021 "Cianjur Lebih Maju dan Agamis" (moreadvance and religious) and Medium Term Development Mission 2016-2021 for the nextfive years is a commitment to achieve the Vision of Cianjur, which is to increasedevelopment in all sectors without any boundaries. It should be recognize that human resources development in the economic field, is a very responsible prominent factor forthe Government of Cianjur in realizing the greatest prosperity for people by equity in afair and equitable target of growth and it can be enjoyed by all citizens for theachievement of Cianjur economical stability. Prospective workers, workers andlaborers are very vital role as actors and gaining economic development goals inCianjur where success is determined by the development of employment, equity andexpansion of employment opportunities as well as the provision of skillful workers andlaborers whose appropriate with the regional development Cianjur needs are thehuman resources manifestation.Keywords: The slogan "Cianjur Jago"; Vision-Mission, Business Participation, LocalGovernment Community of Cianjur Regency; Employment.